Electrochemical Modeling and Performance Assessment of H2S/Air Solid Oxide Fuel Cell - Nurettin Sezer (14778217) (2023)
Hydrogen sulfide (H2S) is an abundantly present, corrosive, and noxious compound. Though the Claus process is effective in processing H2S, it extracts minimal energy from H2S. Solid oxide fuel cell (SOFC) can harvest the chemical energy of H2S to generate electric power. For practical implementations, the performance of H2S/air SOFCs and the potential losses in the system are determined. The present study aims to develop the complete electrochemical model of H2S/air SOFC system and to analyze its performance. The theoretical cell potential of H2S/air SOFC is determined, and the deviations from the theoretical cell potential due to polarization are studied. According to the results, H2S/air SOFC generates electric power with energetic, exergetic, and voltaic efficiencies of 59.0%, 43.0%, and 89.7%, respectively, at atmospheric pressure and a temperature of 1100 K. Further efficiencies can be achieved if the output heat is utilized for useful applications. Moreover, the SO2 formed by the electrochemical reactions in SOFC can be recovered as elemental sulfur or sulfuric acid as an additional useful commodity. In brief, this study demonstrates the performance of H2S/air SOFC to serve as a basis for the implementation of H2S/air SOFC toward eliminating the environmental impact of H2S and converting it into electric power. Other Information Published in: Energy Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ente.202000531